Morphology of gametes, post-fertilization events and the effect of temperature on the embryonic development of Astyanax altiparanae (Teleostei, Characidae) - Santos, Matheus Pereira dos [UNESP]; Yasui, George Shigueki; Porfirio Xavier, Pedro Luiz; Macedo Adamov, Nadya Soares de; Nascimento, Nivaldo Ferreira do [UNESP]; Fujimoto, Takafumi; Senhorini, Jose Augusto; Okada Nakaghi, Laura Satiko [UNESP] (Cambridge Univ Press, 2016)
The aim of this study was to describe the morphology of gametes, post-fertilization events and subsequent temperature effects on the early developmental stages of the neotropical species Astyanax altiparanae. The sperm of this species presents a typical morphology of teleost sperm with a spherical head (diameter = 1.88 mu m), midpiece (diameter = 0.75 mu m) and a single flagellum (length = 18.67 mu m). The extrusion of the second polar body and fusion of male and female pronucleus were reported for the first time in this species. Additionally, we observed the formation of the fertilization cone, which prevents polyspermic fertilization. Developmental stages at 22 degrees C, 26 degrees C and 30 degrees C gave rise to fertilization rates at 91.12, 91.42 and 93.04% respectively. Hatching occurred at 25 hpf at 22 degrees C, 16 hpf at 26 degrees C and 11 hpf at 30 degrees C and the hatching rates were 61.78%, 62.90% and 59.45%, respectively. At 22 degrees C, the second polar body was extruded at approximate to 6 mpf and the male and female pronucleus fused at approximate to 10 mpf. This fundamental information is important for the field and opens up new possibilities in fish biotechnology, including micromanipulation and chromosome-set manipulation.
Keywords: Embryo; Fish; Oocyte; Reproduction; Spermatozoa